2010
DOI: 10.1007/s11426-010-4118-5
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenes as unique nanopharmaceuticals for disease treatment

Abstract: As unique nanoparticles, fullerenes have attracted much attention due to their unparalleled physical, chemical and biological properties. Various functionalized fullerenes with OH, NH 2 , COOH, and peptide modifications were developed. It summarized the biological activities of fullerenes derivatives in cancer therapy with high efficiency and low toxicity, as reactive oxygen species scavenger and lipid peroxidation inhibitor, to inhibit human immunodeficiency virus and to suppress bacteria and microbial at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 65 publications
0
16
0
1
Order By: Relevance
“…This suggests that the reactivity upon electrophilic addition of the fullerenes decreases in the order of C 60 > Gd@C 60 > Gd@C 82 . The ∆Gs for reactions (3) and (5) decrease as compared with that of reaction (1) and simultaneously the ∆Gs for reactions (4) and (6) decrease as compared with that of reaction (2). For comparison, similar reactions of C 60 were also calculated.…”
Section: Gd@c 60 / Gd@c 82 + O 2 In An Alkaline Conditionmentioning
confidence: 99%
“…This suggests that the reactivity upon electrophilic addition of the fullerenes decreases in the order of C 60 > Gd@C 60 > Gd@C 82 . The ∆Gs for reactions (3) and (5) decrease as compared with that of reaction (1) and simultaneously the ∆Gs for reactions (4) and (6) decrease as compared with that of reaction (2). For comparison, similar reactions of C 60 were also calculated.…”
Section: Gd@c 60 / Gd@c 82 + O 2 In An Alkaline Conditionmentioning
confidence: 99%
“…Одним із перспективних шляхів у розробці такої терапії може бути застосування наночасток, які створені на основі фулере-ну С 60 (FC 60 ) [3]. FC 60 -це нова алотропна форма вуглецю, в якій 60 атомів утворюють сферичну молекулу з високою стабільністю, біосумісністю, унікальними фізико-хімічними і біологічними властивостями, які дають змогу активно приєднувати різні радикали, миттєво проходити крізь мембрану клітини без прояву цитотоксичного ефекту [4].…”
Section: вступunclassified
“…6.1). These derivatives present highly attractive nanomaterials for various biomedical applications [7,[21][22][23][24][25][26][27]. In some earlier conducted studies [28], researchers concluded that functionalization of fullerene C 60 under photosensitive conditions decreases its prooxidative properties and makes it less toxic than non-functionalized C 60 [28].…”
Section: Biological Activity Of Derivatized Fullerene C 60mentioning
confidence: 99%
“…However, when it is, via abiotic processes, being transformed into a better water-soluble form [381], carbon cage becomes more susceptible to biological degradation. For example, fullerenol C 60 (OH) [19][20][21][22][23][24][25][26][27] can be oxidized by white rot basidiomycete fungi to CO 2 [382]. Agreggation of fullerene nanoparticles (nC 60 ) is of the utmost importance for its fate and transport in the environment [383], its production of reactive oxygen species [384], toxicity agains microorganisms [13,384], as well as for its sorption capacity of nonpolar organic contaminants (e.g., atrazine and naphtalene) [385,386] (Figure 6.5).…”
Section: Ecotoxicological Effects Of Carbon Nanomaterialsmentioning
confidence: 99%